Sample of learners and teachers perception on the implementation of the affectivity and integral sexuality in the Costa Rican Educational Program - León León, Giselle (2013)
The case study focuses on the relevance of the Affectivity and Integral Sexuality in the Costa Rican Educational Program (EAIS) implementation. This program was proposed by the Ministry of Public Education (MEP) in 2013. It was implemented using a mixed approach under a dominant mixed classification. To gather data for the different study categories (knowledge of the topic, teaching models, and methodological strategies), a questionnaire was applied to nineteen students and some semi-structured interviews were carried out for five Science teachers from a high school within the Costa Rican Metropolitan Area. Some contributions were emphasized in matrices (charts) and contrasted through of triangulation both of theory and participants. Within the main conclusions stands out the relevance of programs for the effectiveness and integral sexuality supported by professionals in education and the learning population of the study. In addition, it was identified that the participants’ ´knowledge of the study (learners and instructors) was merely biological oriented.